Ethnic differences in thromboprophylaxis for COVID-19 patients: should they be considered? - Iba, Toshiaki; Connors, Jean Marie; Spyropoulos, Alex C.; Wada, Hideo; Levy, Jerrold H. (International journal of hematology, 2021)
Thromboembolic events contribute to morbidity and mortality in coronavirus disease 2019 (COVID-19). As a result, thromboprophylaxis using low-molecular-weight heparin (LMWH) is universally recommended for hospitalized patients based on multiple guidelines. However, ethnic differences with respect to thrombogenicity have been reported and the incidence of thromboembolic events is considered to be lower in the Asian population. Despite the importance of thromboprophylaxis, bleeding is also a side effect that should be considered. We examine the data relating to potential ethnic differences in thrombosis and bleeding in COVID-19. Although sufficient data is not yet available, current evidence does not oppose routine anticoagulant use and thromboprophylaxis using a standard dose of LMWH for admitted patients regardless of ethnicity based on our review.